Giving Brain Gym Using Booklets To Reduce The Level Of Depression Among Elderly In The Community - Wachidah Yuniartika; Kartinah Kartinah; Niken Enggal Dwi Astuti (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
The number of older adults found in Indonesia, as many as 30% claimed to have depression syndrome. Depression syndrome shows mood disorders, physical and cognitive symptoms. Cognitive symptoms can include difficulties in making decisions, decreased concentration, and physical symptoms. One of the management of depression is psychotherapy using brain gymnastics. Brain Gym has the benefit of activating the three dimensions of the brain, namely the concentration dimension, the lateral dimension, and the focusing dimension.This research method was quantitative by using a pre-experimental design with the Quasi-experiment pretest-posttest design without control group design. The research site was in the Posyandu for the elderly in Pabelan Village, Kartasura District, Sukoharjo, Central Java, with a time of March 1 - April 4, 2019, as many as 30 sites with a purposive sampling method. The inclusion criteria for respondents were aged over 60 years, experiencing mild and moderate depression, not on an anti-depressant, anti-psychotic, or anti-anxiety treatments. This research used the Geriatric Depression Scale (GDS) short form instrument and the Paired t-test.The results of the study obtained data that from the results of the pre-test, majority of respondents were Minor Depression (93.3%), from post-test 1, majority not Depressed (66.7%), and from the Post-test 2, majority Not Depressed (83.3%). The p-value of posttest 1 was 0.039, and posttest 2 was 0.001. The conclusion is that there is a significant influence in the provision of Brain Gymnastics in posttest 2, with a P-value of 0.001. The level of depression in the elderly results in the mean value of the pretest is higher than the value of the posttest, which means that the level of depression after brain gym therapy has decreased.